'Message for Posterity': The Singing Detective (1986) 25 years on. (1st August 2013) - Cook, John R.
This article offers a reappraisal of Dennis Potter's television script for The Singing Detective (BBC, 1986) in the 25th anniversary period of the production's first broadcast. The article reviews the history of the author's intellectual engagement with The Singing Detective – of what it meant to him then, when he first saw the production in 1986 and of what it means to him now. It discusses the relationship of The Singing Detective to literary modernism, particularly James Joyce's novel, Ulysses published in 1922. It examines debates on whether Potter is a postmodern writer and also explores the relationship of The Singing Detective to psychoanalysis. It concludes by arguing that Potter's TV screenplay for The Singing Detective is best seen as a religious work in which spirituality is redefined as the capacity for human beings to reshape their own reality. In this lies Potter's Christian optimism and The Singing Detective stands as his message for posterity in this regard.